Potential trade distortion effects of state trading enterprises under the tariff-rate quota scheme - Jung-Hyun Yoon; Song Soo Lim (Kiel Institute for the World Economy (IfW), 2013)
The paper analyzes the potential trade distortion effects of state trading enterprises (STEs) on soybean imports to Korea. Traditionally, STEs have exercised exclusive rights to import the so-called strategic products, to ensure food security, domestic price stabilization, and import mark-ups. However, STE imports have been criticized on the grounds that industries using soybeans as a raw material are unable to obtain a diverse mix of quality material and cannot exercise the right to choose their own ingredients. Under a theoretical framework, a tariff equivalent of the STE is postulated to equate imports by private firms with imports by the STE. An empirical model is constructed and estimated using annual data spanning 1980-2009. The estimated results show that providing exclusive rights to imports has a negative effect on market access. When the STE pursues consumer welfare, the import-reducing effect turns out to be smaller than that in the producer welfare maximization case.
Keywords: F11; F13; Q17; 330; state trading enterprises; tariff-rate quotas; tariff equivalents; soybeans; sensitive products